PELATIHAN PEMASARAN PRODUK DAN LAPORAN KEUANGAN SEDERHANA BAGI PELAKU USAHA WISATA SUSUR SUNGAI DI PALANGKA RAYA - Ferdinand Ferdinand; Vivy Kristinae (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This community service activity aims to improve the knowledge and skills of tourism business actors in Palangka Raya, especially in the Kahayan River Tourism area, in the field of product marketing and the preparation of simple financial reports. Kahayan River Trail Tourism is one of the leading tourism potentials in Palangka Raya City that offers the experience of enjoying the beauty of the Kahayan River through boats or klotok, with natural attractions, culture, and life of the riverside community. The Palangka Raya City Tourism, Culture, Youth and Sports Office describes the Kahayan River as a path that has strong historical, cultural, and natural charm values for the city of Palangka Raya. The problems faced by tourism business actors include limited ability to market tourism products, lack of optimal use of digital media, orderly financial records, and the lack of simple financial reports that can be used to evaluate businesses. The activity method uses a qualitative descriptive approach through observation, interviews, socialization, training, discussions, practices, and evaluation of activities. The results of the activity showed that the training was able to increase participants' understanding of tourism product marketing strategies, preparation of promotional content, consumer services, recording income and expenses, and the preparation of simple profit and loss reports. This activity is expected to strengthen the capacity of tourism business actors in developing businesses in a more planned, professional, and sustainable manner.